Investigation of Blast Effects on Double-Skinned Composite Steel Tubular Columns. Issue 3 (September 2015) - Zhang, Huidong; Li, Zhongxian; Wu, Chengqing
In recent years, concrete filled double skin steel tube (CFDST) members have gained interest due to its attractive properties such as ease of construction, light weight, high strength and good seismic resistance, and thus it is expected that these members have the potential of being used in construction of buildings. However, there is lack of understanding about the inelastic behaviors of CFDST members under blast loads. In this paper, based on the ConWep airblast loading model, the blast resistance of typical circular CFDST columns used in engineering field is investigated and the multiple failure modes of CFDST columns under blast loading are analyzed. The influence of explosive charge weights and column axial loading condition on the response of CFDST columns are investigated through parametric study. Finally, the direct shear and flexural failure modes of CFDST columns are analyzed, and uncoupled P-I (pressure-impulse) diagrams are obtained based on an equivalent single degree of freedom (SDOF) system. This study helps to understand the non-linear behaviors of CFDST columns subjected to blast loading.